EXPERIENCES ON THE DEVELOPMENT OF AN INDIGENOUS AFRICAN LANGUAGE SCIENTIFIC REGISTER FOR NATURAL SCIENCES: A FOCUS ON CHALLENGES, OPPORTUNITIES, AND PERCEPTIONS - Thuli G. Ntuli; Awelani V. Mudau (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This is a qualitative interpretative case study. The aim of this article is to elucidate the experiences on the development of an African indigenous language (IsiNdebele) scientific register for natural sciences. Interviews and a diary were used to collect data from stakeholders. The results of the study reveal that isiNdebele is still underdeveloped as it lacks scientific terms and different perceptions held by stakeholders on the use of isiNdebele scientific language register to teach Natural Sciences. Some stakeholders are in support of the use of the isiNdebele scientific language register to teach Natural Sciences as learners will be able to learn in their mother tongue which could be beneficial to them. However, with all the research findings on the benefits of using mother tongue as a medium of teaching and learning in South African schools. There are still stakeholders who are not in support of using isiNdebele scientific language register as they still prefer English as a medium of instructions due to its state and being a language of economy and power. Their perceptions further determine and threatens the survival of these indigenous languages. It is therefore recommended that scientific language registers be developed in indigenous languages. With these scientific languages registers in indigenous languages being developed stakeholders might change their perceptions on the use of African languages as languages of teaching and learning.